Characterisation of electrically active defects. Issue 1 (25th November 2013) - Duffy, Ray; Heringa, Anco; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract Defects may arise in the semiconductor substrate and at interfaces due to the processing used to fabricate transistors and circuits. The development of low‐thermal‐budget processes, which is advantageous in many ways, unfortunately reduces the likelihood of annealing out these electrically active defects. Electrical characterisation using simple diode structures yields valuable information; not only the absolute leakage current density value, but also carrier lifetimes, leakage activation energies, and diode ideality factor. Coupled with material analysis techniques, they can provide a detailed picture of the problems associated with process‐induced defects, and supply insight that can target optimised processes. In this paper the technological relevance of electrically active defects, their impact on device performance and power supplies, as well as their electrical and material characterisation, will be discussed. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)